2015
DOI: 10.1111/1462-2920.12967
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the abilities of Agaricus bisporus to degrade plant biomass throughout its life cycle

Abstract: The economically important edible basidiomycete mushroom Agaricus bisporus thrives on decaying plant material in forests and grasslands of North America and Europe. It degrades forest litter and contributes to global carbon recycling, depolymerizing (hemi-)cellulose and lignin in plant biomass. Relatively little is known about how A. bisporus grows in the controlled environment in commercial production facilities and utilizes its substrate. Using transcriptomics and proteomics, we showed that changes in plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
62
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 48 publications
8
62
1
Order By: Relevance
“…Partial degradation of easily accessible hemicelluloses likely provides the energy for lignin degradation (Blanchette 1984), while production of polysaccharide degrading enzymes increases gradually when these polysaccharides become more accessible by removal of lignin (Pandey & Singh 2014). This has also been observed for other basidiomycete white-rot fungi (Patyshakuliyeva et al 2015, Kuuskeri et al 2016). The results of our study also show that white-rot fungi in both monokaryotic and dikaryotic forms use a similar strategy for plant biomass degradation.…”
Section: Discussionsupporting
confidence: 78%
“…Partial degradation of easily accessible hemicelluloses likely provides the energy for lignin degradation (Blanchette 1984), while production of polysaccharide degrading enzymes increases gradually when these polysaccharides become more accessible by removal of lignin (Pandey & Singh 2014). This has also been observed for other basidiomycete white-rot fungi (Patyshakuliyeva et al 2015, Kuuskeri et al 2016). The results of our study also show that white-rot fungi in both monokaryotic and dikaryotic forms use a similar strategy for plant biomass degradation.…”
Section: Discussionsupporting
confidence: 78%
“…The S/G ratio changed from 0.38 in PII-end compost to 0.47 and 0.43 at venting and after the 2nd flush, respectively. This pattern agrees with previous reports (Zeng et al 2011; Jurak et al 2015; Patyshakuliyeva et al 2015). However, ligninolytic activity in other systems has been associated with a decrease rather than an increase of the S/G ratio (Camarero et al 2001; Martinez et al 2001; Vane et al 2001a, 2001b; del Rio et al 2002; Geib et al 2008).…”
Section: Discussionsupporting
confidence: 94%
“…From this it is concluded that A. bisporus affects lignin differently in PIV as compared to PIII, specifically during mushroom formation. This is associated with an increase in cellulase and hemicellulose activity and a decrease in ligninolytic activity during fruiting (Wood and Goodenough 1977; Bonnen et al 1994; Patyshakuliyeva et al 2015). Notably, the Ph-C1,2/Ph-C3 ratio had increased after the 2nd flush for compost colonized by A15 but not for compost colonized by MnP1-1.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, A. bisporus did not degrade these remaining substituted xylan fragments. That conclusion was supported by the result that the two genes annotated as putative ␣-glucuronidases (both GH115, Patyshakuliyeva et al, 2013Patyshakuliyeva et al, , 2015 were not expressed in the same compost samples as used to analyze the resistant substituted xylans. In addition, A. bisporus genes from family GH43 were assessed for similarity to two genes known to encode biochemically characterized AXH-d3 activity featuring the release of arabinose from xylosyl residues doubly substituted with arabinosyl residues.…”
Section: Discussionmentioning
confidence: 83%
“…The phylogenetic analysis, RNA extraction, cDNa library preparation and RNA seq was performed as described by Patyshakuliyeva et al (2015).…”
Section: Molecular Analysismentioning
confidence: 99%